2016
DOI: 10.1007/s11225-016-9677-9
|View full text |Cite
|
Sign up to set email alerts
|

Cofinal Stable Logics

Abstract: We generalize the (∧, ∨)-canonical formulas to (∧, ∨)-canonical rules, and prove that each intuitionistic multi-conclusion consequence relation is axiomatizable by (∧, ∨)-canonical rules. This yields a convenient characterization of stable superintuitionistic logics. The (∧, ∨)-canonical formulas are analogues of the (∧, →)-canonical formulas, which are the algebraic counterpart of Zakharyaschev's canonical formulas for superintuitionistic logics (si-logics for short). Consequently, stable si-logics are analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…These rules were recently introduced in [1], where it was shown that each normal modal multi-conclusion consequence relation is axiomatizable by stable multi-conclusion canonical rules. The same result for intuitionistic multi-conclusion consequence relations was established in [2].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…These rules were recently introduced in [1], where it was shown that each normal modal multi-conclusion consequence relation is axiomatizable by stable multi-conclusion canonical rules. The same result for intuitionistic multi-conclusion consequence relations was established in [2].…”
Section: Introductionsupporting
confidence: 73%
“…Now assume that a transitive modal space (W, R) does not validate (2). We show that then it does not validate (1).…”
Section: Proof Let ρ(A D) Be the Rulementioning
confidence: 90%
See 1 more Smart Citation
“…For more in-depth development of the theory of stable modal systems see [5]. The theory of stable superintuitionistic logics and stable intuitionistic multi-conclusion consequence relations is developed in [3,4].Stable canonical rules have several applications. For example, they are utilized in [10] to obtain an alternative proof of the existence of explicit bases of admissible rules for the intuitionistic logic, K4, and S4.…”
mentioning
confidence: 99%
“…For more in-depth development of the theory of stable modal systems see [5]. The theory of stable superintuitionistic logics and stable intuitionistic multi-conclusion consequence relations is developed in [3,4].…”
mentioning
confidence: 99%